Practices and knowledge of health personnel about transgenderity in Primary Health Care - Francisco Jean Gomes de Sousa; Edgar Amatuzzi; Andressa Teoli Nunciaroni; Jaime Alonso Caravaca-Morera; Claudia Regina Ribeiro; Adriana Lemos (Atención Primaria)
Objective: To describe the practices and knowledge of Nursing Technicians and Community Health Agents of Primary Health Care for the transgender population. Design: Descriptive research with a qualitative approach. Site: The study was developed in a digital environment. Participants: 18 Community Health Agents and 12 Nursing Technicians who worked in Primary Health Care Units from several Brazilian states. Method: Sampling technique by chain indication or networks (snowball), data production by Google Forms form. The theoretical saturation technique was used to close the interviews. Categorical thematic content analysis with IRAMUTEQ software support. Results: Professionals’ lack of knowledge about policies and terms was evidenced; there were conceptual confusions, inadequate associations, and a restricted approach to the prevention of sexually transmitted infections. Conclusions: The lack of training reflects a cisnormative and binary approach, compromising the assistance to the transgender population. Disrespect for the social name persists, highlighting the need for permanent education for health professionals, aiming at an inclusive and respectful care practice. Resumen: Objetivo: Describir las prácticas y los conocimientos de los técnicos de enfermería y agentes comunitarios de salud de atención primaria sobre la población transexual. Diseño: Investigación descriptiva con enfoque cualitativo. Emplazamiento: El estudio se desarrolló en un entorno digital. Participantes: 18 agentes comunitarios de salud y 12 técnicos de enfermería que trabajaban en unidades de atención primaria de salud de varios estados brasileños. Método: Técnica de muestreo por indicación en cadena o redes (bola de nieve) y producción de datos mediante formulario Google Forms. Para el cierre de las entrevistas se utilizó la técnica de saturación teórica. Análisis de contenido temático categorial con apoyo del software IRAMUTEQ. Resultados: Se evidenció desconocimiento de políticas y términos por parte de los profesionales, confusiones conceptuales, asociaciones inadecuadas y un abordaje restringido de la prevención de las infecciones de transmisión sexual. Conclusiones: La falta de capacitación refleja un abordaje cisnormativo y binario que compromete la asistencia a la población transexual. Persiste la falta de respeto al complejo social, resaltando la necesidad de educación permanente de los profesionales de salud, con el objetivo de una práctica asistencial inclusiva y respetuosa.